Late, lost, and unprepared : a parents' guide to helping children with executive functioning - Cooper-Kahn, Joyce; Dietzel, Laurie C. (New York, NY : Routledge, 2024)
"Does your child have difficulty meeting deadlines, staying organized, or keeping track of important information? Do they tend to forget details? Are they prone to emotional meltdowns? This book will become your go-to, all-inclusive guide to helping children manage issues with these executive functions, a set of related yet distinct mental skills that allow us to stay on target as we work toward our goals. Packed with encouragement, strategies, overviews, case studies, tips, and more, this newly revised edition offers science-based information explained in accessible, everyday language. You will find down to earth examples and a flexible framework that allows you to think on your feet and adapt the strategies to any child or situation. In addition to providing approaches for helping your child to manage demands in the short run, this book offers strategies for building independent skills for long-term self-management. Covering what you need to know, as well as what you can do, Late, Lost, and Unprepared gives parents the support they need to help their child become productive and independent - today and in the future"--
Introduction -- What is executive functioning? -- Development of the executive functions -- The child's experience of executive weaknesses -- Impact on the family -- Assessment : figuring out what's needed -- ADHD, learning disabilities, and other conditions associated with executive functioning challenges -- How to help : an overview -- Behavior change in a nutshell -- If at first you don't succeed, try a few more times then ... change your expectations! -- Helping children control impulses -- Helping children shift gears -- Helping children get started on homework and other tasks -- Helping children with working memory challenges -- Helping children to plan and organize -- Helping children monitor their behavior -- Special topic : helping children with emotional regulation -- Concluding thoughts.
Keywords: Executive ability in adolescence; Executive ability in children; Self-management (Psychology) for teenagers; Self-management (Psychology) for children; Self-control in adolescence; Self-control in children; Attention in adolescence; Attention in children; EDUCATION / General; FAMILY & RELATIONSHIPS / Learning Disabilities